Nova reforma do ensino médio (Lei nº 13.415/17): desvelando a proposta curricular do estado da Paraíba - Gomides, Fernanda de Paula (2022)
In the middle of a political, economic and social crisis in Brazil, especially since 2016, substantial changes are being implemented in education. One of these changes, which deserves to be evaluated, is the approval of the Novo Ensino Médio (NEM) in Brazil, resulting from the approval of Lei nº 13.415/2017. This law obliges all states of the Union to develop state curriculum proposals aligned with the BNCC. Based on this, the general objective of this research is to analyze the curricular proposal in the state of Paraíba, considering the persistent and historical educational dualism represented in the law and curricular proposals. Regarding the specific objectives, we seek, in addition to a historical discussion about such policies and the current reform: investigate the crisis in the professional world, starting in 1970, and its impacts on education, including in Latin America; identify the educational policies historically formulated in Brazil, especially for High School, from 1930 onwards; examine the formulation and institution of the Reforma do Novo Ensino Médio in Brazil; analyze the implementation of the reform in the state of Paraíba based on Lei nº 13.415/2017 and on documents/proposals of the Conselho Estadual de Educação na Paraíba (CEE/PB). Based on the understanding of the relationship between State and society, capital and work, we base ourselves on the theoretical-methodological contribution of the scientific method of dialectical historical materialism (especially dealing with categories such as contradiction and totality) and historical-critical pedagogy. As main sources, Law nº 13.415 of 2017 is defined (which modified the LDBEN/1996 and appropriated the fundamentals of the BNCC/EM of 2018), accompanied by the documents of the CEE/PB, particularly the versions of the curricular proposal of the Paraíba state. We point out here that we analyze the curricular proposals emphasizing the area of knowledge in human sciences, as well as the formative itinerary of the same area, in view of our academic training, which allows for greater fluidity of analysis. Based on this work, we understand that we not only do not overcome, but also encourage – with this curricular reform – the historical educational dualism present in the country, with regard to the difference between public education (adjusted for the working class in the production of hand of work) and the private one (modulated for access to the educated knowledge of the elite). We consider the Law 13,425/17 as a step backwards in terms of streamlining student training, with the aim of meeting the labor market and international and institutional assessments. The proposal from Paraíba, even based on the reform imposed without dialogue with society and with global/neoliberal influences, moved towards a bias that was more in line with the ideals of popular education, of criticism of the influences of international organizations and external evaluations, and with a focus on training more socially conscious young people. There is, in the document from Paraíba, a broad effort to constitute a democratic and inclusive proposal, but when it is aligned with the neoliberal pillars already mentioned in previous documents, such as the BNCC, the transformative limitation of the proposal is clear.